Perceived challenges caused by Covid-19 outbreak in students of medical sciences - Nayereh Baghcheghi; Hamid Reza Koohestani; Mahmood Karimy; Mohammad Hasan Keshavarzi; Ali Asghar Ghorbani (Wolters Kluwer Medknow Publications, 2022)
Background: Students of medical sciences are a highly vulnerable group during COVID-19 pandemic who may experience a wide range of challenges and stresses. The aim of this study was to investigate the perceived challenges caused by COVID-19 outbreak in students of medical sciences. Materials and Methods: A qualitative study was carried out based on conventional qualitative content analysis following Graneheim and Lundman from December 2020 to February 2021. The participants were 17 students of medical sciences and data gathering was done through semistructured interviews. Results: Data analyses revealed 5 categories and 12 subcategories. The extracted categories were perceived fear of contracting coronavirus, social limitation, changes in education, neglecting health protocols, and worrying news and information overload. Conclusions: The findings indicated that students of medical sciences had been facing challenges and the COVID-19 had affected the psychological, social, and academic functioning of the health-care students. It is important to take measures to improve their mental health. These measures can prevent medical complications in these students, especially during clinical internship.